2020
DOI: 10.5456/wpll.22.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Reframing widening participation towards the community: a realist evaluation

Abstract: This article draws on an evaluation of Go Higher West Yorkshire (GHWY) Uni Connect – an initiative by the Office for Students (OfS) to reduce educational inequalities through collaborative widening participation (WP) outreach across West Yorkshire. It contributes to wider debates on widening participation policy through demonstrating how Higher Education Progression Officers (HEPOs) normalised 'progression' based on community and learners' needs. We deploy realist evaluation to examine the role of HEPOs in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Interestingly, in addition to the benefits associated with being exposed to workplaces, in the context of disengaged young people who had never attended a higher educational institution, exposure to a university campus enabled a number of young people to feel more comfortable within the university environment and to imagine themselves as a university student. This finding is consistent with previous work which has suggested that university visits can allow disengaged young people to gain knowledge, perspective, and experience regarding university life, and may, in turn, enhance their intentions to attend university and pursue higher education (Fleming & Grace, 2015;Formby, Woodhouse, & Basham, 2020;Whitley et al, 2017). Such findings are particularly important given that many disengaged young people are often from low socio-economic families and are underrepresented in higher education (DfE, 2020).…”
Section: Initial Programme Theory 4: the Importance Of A Youth-driven Multi-component Programmesupporting
confidence: 92%
“…Interestingly, in addition to the benefits associated with being exposed to workplaces, in the context of disengaged young people who had never attended a higher educational institution, exposure to a university campus enabled a number of young people to feel more comfortable within the university environment and to imagine themselves as a university student. This finding is consistent with previous work which has suggested that university visits can allow disengaged young people to gain knowledge, perspective, and experience regarding university life, and may, in turn, enhance their intentions to attend university and pursue higher education (Fleming & Grace, 2015;Formby, Woodhouse, & Basham, 2020;Whitley et al, 2017). Such findings are particularly important given that many disengaged young people are often from low socio-economic families and are underrepresented in higher education (DfE, 2020).…”
Section: Initial Programme Theory 4: the Importance Of A Youth-driven Multi-component Programmesupporting
confidence: 92%
“…We are therefore treating the programme as a pilot to explore and test how best to support prospective students and their families from BAME communities into HE. As there is limited evidence of what works for this specific student group, we ensured that comprehensive mixed methods evaluation was developed as part of the programme, starting with its design (via our Theory of Change Initiative Planning Document) so that we can truly evaluate what works, for whom and in what circumstances (Formby et al, 2020).…”
Section: Mixed Methods Programme Evaluationmentioning
confidence: 99%
“…Realist evaluation has gained credence as a methodological framework for evaluating complex initiatives such as the OHD (see Dytham and Hughes 2017;Formby, Woodhouse, and Basham 2020;Ryan 2020;Pickering 2021). Realist evaluation affords a degree of pragmatism, in which it eschews simplistic notions of programme success or failure; instead, it seeks to uncover the conditionalities and contextualities of a programme, exploring what worked for whom, in what circumstances and why (Pawson and Tilley 1997).…”
Section: Introductionmentioning
confidence: 99%